A Biomechanical Comparison of Three 1.5-mm Plate and Screw Configurations and a Single 2.0-mm Plate for Internal Fixation of a Mandibular Condylar Fracture. Issue 3 (September 2014) - Aquilina, Peter; Parr, William C.H.; Chamoli, Uphar; Wroe, Stephen; Clausen, Philip
The most stable pattern of internal fixation for mandibular condyle fractures is an area of ongoing discussion. This study investigates the stability of three patterns of plate fixation using readily available, commercially pure titanium implants. Finite element models of a simulated mandibular condyle fracture were constructed. The completed models were heterogeneous in bone material properties, contained approximately 1.2 million elements and incorporated simulated jaw adducting musculature. Models were run assuming linear elasticity and isotropic material properties for bone. No human subjects were involved in this investigation. The stability of the simulated condylar fracture reduced with the different implant configurations, and the von Mises stresses of a 1.5-mm X-shaped plate, a 1.5-mm rectangular plate, and a 1.5-mm square plate (all Synthes (Synthes GmbH, Zuchwil, Switzerland) were compared. The 1.5-mm X plate was the most stable of the three 1.5-mm profile plate configurations examined and had comparable mechanical performance to a single 2.0-mm straight four-hole plate. This study does not support the use of rectangular or square plate patterns in the open reduction and internal fixation of mandibular condyle fractures. It does provide some support for the use of a 1.5-mm X plate to reduce condylar fractures in selected clinical cases.